2012
DOI: 10.1074/jbc.m112.376053
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of TM3-4 Loop Subdomains for Functional Reconstitution of Glycine Receptors by Independent Domains

Abstract: Background: Truncated non-functional GlyRs are reconstituted in channel function by co-expression with a C-terminal domain. Results: TM3-4 loop residues are expressed independently of TM4 and the truncated GlyR. Conclusion: TM4 and the C terminus are not sufficient to rescue GlyR function; rather, residues of the TM3-4 loop are required. Significance: TM3-4 loop residues trigger directly or indirectly conformational changes necessary for GlyR functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The reduced glycine sensitivity was only partly compensated by co-expressing the ␤ wild type subunit. This result strongly suggests that the truncated subunit is incorporated into functional receptors, which is unexpected given that previous GlyR studies indicated that TM4 deletion is incompatible with the surface expression of functional ␣1 GlyRs (32)(33)(34)(35). Given our unexpected result, we sought to confirm whether the p.E375X mutant subunit was incorporated into functional GlyRs using voltage clamp fluorometry.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The reduced glycine sensitivity was only partly compensated by co-expressing the ␤ wild type subunit. This result strongly suggests that the truncated subunit is incorporated into functional receptors, which is unexpected given that previous GlyR studies indicated that TM4 deletion is incompatible with the surface expression of functional ␣1 GlyRs (32)(33)(34)(35). Given our unexpected result, we sought to confirm whether the p.E375X mutant subunit was incorporated into functional GlyRs using voltage clamp fluorometry.…”
Section: Resultsmentioning
confidence: 87%
“…We also attempted to confirm it using immunofluorescence, but the incorporation rate may have been too low to allow surface expression to be detected. As noted above, we were surprised that the p.E375X subunit was incorporated, given that previous studies have shown that TM4 deletion is incompatible with the surface expression of functional ␣1 GlyRs (32)(33)(34)(35). Indeed, the deletion of only a few residues at the C-terminal end of the TM4 domain is sufficient to render some pLGIC receptors completely nonfunctional (12,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Following 48 h post-transfection, biotinylation experiments were performed from transfected HEK293 cells as described previously [11]. Whole cell and surface fractions were stained using MAb4A for GlyR␣ receptor protein and a pan-cadherin antibody (Cell Signaling, Danvers, MA, USA) to stain cadherin as a membrane marker.…”
Section: Biotinylation Of Cell Surface Proteinmentioning
confidence: 99%
“…The Gly receptor domain architecture does also allow for the generation of a functional inhibitory neurotransmitter receptor from three independent domains. The co‐expression of the lacking M3–M4 loop in addition to the truncated N‐ and C‐terminal Gly receptor α1 protein fragments again resulted in the rescue of channel function (Figure C) (Unterer et al ., ).…”
Section: Domain Co‐expression: a Way To Rescue Protein Functionmentioning
confidence: 97%